Correlation Between the Anticorrosive Performance of Protective Coatings Under Neutral Salt Spray Testing and Outdoor Atmospheric and Immersion Exposure - Matthias J. Schmid (Corrosion and Materials Degradation)
Anticorrosive organic coatings are usually tested with accelerated weathering methods to assess their anticorrosive performance. The results of lab testing often do not correlate well with results from field testing, which resembles the conditions of actual use more closely. We tested the correlation of the neutral salt spray test (NSS, ISO 9227) and tests for mechanical properties and a 5-year field exposure in four different locations in the atmospheric zone, splash zone and immersion zone using 19 organic coatings for hydraulic steelwork. No correlation was found between the anticorrosive performance under outdoor exposure and the mechanical properties of a coating. The NSS test showed a positive correlation with the results in the field in 6 of 12 cases. For the fresh water testing location in Trier, the correlation proved to be very good. The biggest difference between lab and field testing was observed for zinc-primer-free coatings, which passed in the lab testing and failed in the outdoor testing. This study shows that the NSS test correlates with outdoor exposure only in some cases on a statistically significant level, but the results of NSS testing can be useful in approval testing for protective coating systems using predefined pass/fail criteria.